DETERMINATION OF POTASSIUM AND SILICON FROM LEFT-OVER OF GOLD ORE USING PROTON INDUCED X-RAY EMISSION (FUDMA JOURNAL OF SCIENCES, 2023)
The purpose of this study is to determine potassium and silicon concentrations (K & Si) in five geological samples using proton induced x-ray emission. PIXE was first introduced by Johansson, at the Lund Institute of Technology in 1970 using MeV proton beams and high resolution Si(Li) detector. It is a highly sensitive, multi-elemental analytical technique which has been well utilized in areas such as thin films, water, air, archaeological, biological and geological samples etc. It was employed in this work to characterize these geological samples collected from maga mining site. Samples were irradiated with proton beam of energy ranged from 2-3 MeV, accelerated by 1.7 MeV Tandem accelerators at Centre for Energy Research and Development, Ile-Ife, Nigeria. The characteristic X-rays emitted from the samples as a result of irradiation were detected with Si(Li) detector. The number of emitted X-rays with characteristic energy peak is a measure of elemental concentration for specific element present in the samples. The spectrum obtained is stored for qualitative and quantitative calculation at a later date using GUPIX software. The potassium and silicon alongside with other elements Fe, S, P, Ti, Ca, Cr. Ba, Sr, Zr, Cu, Rb, Zn, Sr, and Ni were determined. The results obtained indicated that potassium and silicon is of commercial deposit at the regions. The Fe concentrations appear to be deposited in commercial quantities in the area. The health implication of silicon’s high concentration causing silicosis of lungs upon inhalation. This problem is
Keywords: Ile-Ife, maga and PIXE